The effect of natural radioactivity on diatom communities in mineral springs. Issue 1 (2nd January 2020) - Millan, Fanny; Izere, Cheilla; Breton, Vincent; Voldoire, Olivier; Biron, David G.; Wetzel, Carlos E.; Miallier, Didier; Allain, Elisabeth; Ector, Luc; Beauger, Aude
ABSTRACT: Diatoms are good indicators of water quality because of their great diversity and wide ecological range. They are also interesting in assessing the impact of radioactivity on ecosystems because of their capacity to absorb radioelements. They also show radio-induced deformities, observed in many species. In order to assess more precisely the impact of natural radioactivity, diatom communities were monitored during a 9-month survey in two mineral springs characterized by radioactivity levels ranging within two orders of magnitude. The experimental data obtained were analyzed using different multivariate and clustering analyses. The richness was high with the dominance of Planothidium frequentissimum and Crenotia angustior . In the most radioactive spring known in Auvergne (above 4000 Bq L −1 radon activity), the average deformation was 24.7%, in contrast with lower teratological rates observed in the less radioactive spring. In the absence of heavy metals, this result confirmed that radioactivity is an environmental stress for the diatoms living in these particular ecosystems. This conclusion was reinforced by the selection of springs from a database of 126 ecosystems comparable to our studied sites except the lower level of radioactivity. In these "mirror" springs, few deformations were observed.